PEMODELAN 2D SEBARAN TAHANAN JENIS TERHADAP KEDALAMAN DAERAH PANASBUMI GARUT BAGIAN SELATAN MENGGUNAKAN METODE MAGNETOTELLURIK - Dita Destyanti; Tony Yulianto; Eddy Z Gaffar (Youngster Physics Journal, 2016)
Southern Garut geothermal area West Java, is one of the area with geothermal prospects, characterized by the surface manifestations of craters in Papandayan mountain region and hot springs in Ciarinem area. The area was composed by old volcanic rocks, generally consists of a tuff rocks, tuff breccias and lava. This study aims to interpret 2D modeling of resistivity distribution to the depth of Garut Southern area geothermal and to determine geothermal system of that area under magnetotelluric method (MT). This method is used because its capablility to detect subsurface structure to a thousand meters depth. The data was taken as much as 32 acquisition points. The Data was obtained from field acquisition process, further processed using SSMT 2000 MT Editor 90, and WinGLink software. The results showed the presence of two geothermal systems in Ciarinem and Papandayan mountain region, consist of clay cap rocks, reservoir rocks, and hot rock. Clay cap rocks wich tend conductive located at shallow depths with resistivity value ranging from 10 – 30 ohm.m, reservoir rocks with resistivity value of between 40 – 600 ohm.m and hot rocks that are more resistive have resistivity value ≥700 ohm.m.